Learning Hebrew by Writing in English - Jacobson, Rolf A. (Teaching theology and religion, 2011)
This essay explores a midrange teaching and learning issue regarding the teaching of biblical languages and one strategy for addressing the issue. Seminary students do not yield a great enough return in exchange for the investment they are required to make in learning biblical languages. Students invest great time and money, but they do not learn to use the biblical languages to think critically about the Bible. This essay argues that a fruitful strategy for addressing this midrange issue is to require students to write in English about the Hebrew language. This strategy fosters students' ability to think critically about the biblical text. It also fosters their ability to use their budding knowledge of a biblical language to engage questions of meaning and issues of interpretation.